Entirely S-protected silicone oil as second generation mucoadhesive agent. (March 2016) - Partenhauser, Alexandra; Zupančič, Ožbej; Podričnik, Snežana; Rohrer, Julia; Leichner, Christina; Bernkop-Schnürch, Andreas
Graphical abstract: Highlights: S-protected silicone shows superior adhesion to intestinal and conjunctival mucosa. The novel thiomer can be ascribed with a potential mucoprotective and antioxidative effect. Pharmaceutical ambits might be mucosal targeting and treatment of inflammations. Abstract: Aim: Design of entirely S-protected silicone oils providing superior mucoadhesion and potential mucoprotection. Methods: 2-Mercaptonicotinic acid (MNA) and its dimer (MNA–MNA) were coupled to amino-modified silicone oil. Thiolated and S-protected silicone oil were assessed regarding rheological mucus interaction, mucoadhesion and potential mucoprotection. Results: For thiolated silicone–MNA and S-protected silicone–MNA–MNA almost quantitative coupling efficiencies could be achieved with total MNA amounts of 193 ± 15 μmol/g and 398 ± 44 μmol/g, respectively. Especially for S-protected silicone oil a firm mucus interaction was determined with an up to 28-fold increase in viscosity in comparison to non-thiolated control. Both silicone thiomers showed enhanced mucoadhesive features with remaining amounts of 18.1 ± 2.5% for silicone–MNA and 44.9 ± 4.8% for silicone–MNA–MNA after 8 h on intestinal mucosa, whereas non-thiolated control was washed away within 4 h. In view of a potential mucoprotective effect, methylene blue release was below 15% for silicone–MNA–MNA upon 8 h of incubation on intestinal and conjunctival mucosa in contrast to 100% leakage for the control. Conclusion: Entirely S-protected silicone oil as second generation mucoadhesive can be ascribed with outstanding mucoadhesion and mucoprotective potential, which renders it a promising tool for mucosal targeting and inflammation treatment modalities.